The Attitudes of People Towards the Prevention and Treatment of Coronavirus COVID-19 According to the Four Noble Truths - Thongvijit, Phrakhrusripariyativitan (Arts of Management Journal, 2020)
The purposes of this research were 1) to study the attitudes of people towards the prevention and treatment of Coronavirus COVID-19 according to the Four Noble Truths, 2) to present the ways to prevent and treat Coronavirus COVID-19 according to the Four Noble Truths. The study was a mixed research method. The researcher used the research questionnaire to collect quantitative data from the samples of 151 respondents and collected qualitative data through interviewing 5 scholars. The statistics used in this research consisted of Frequency, Percentage, Mean and Standard Deviation. Descriptive analysis was used to analyze qualitative data. The results of the research were as follows: The overall attitudes of people towards the prevention and treatment of Coronavirus COVID-19 according the Four Noble Truths were at high level. In particular, the attitudes of people about the ways to prevent Coronavirus COVID-19 were at the highest level, followed by attitudes about the effects of Coronavirus COVID-19, attitudes about the treatment of Coronavirus COVID-19, and attitudes about the causes of Coronavirus COVID-19. The ways to prevent and treat Coronavirus COVID-19 according to the Four Noble Truths are as follows: Being aware and understanding of Coronavirus COVID-19, avoidance and prevention of the causes of Coronavirus COVID-19, setting goals in the prevention and treatment of Coronavirus COVID-19, and following appropriate ways in the prevention and treatment of Coronavirus COVID-19 such as wearing mask, social distancing, avoidance of going to crowded places, and strengthening the mind, and so on.